Evaluation of cardiac murmurs in 8647 children at primary school-age children in the Province of Malatya, Eastern Turkiye - Feyza Aysenur Pac; Hamza Karabiber; Ayhan Kilic; Onur Kutlu; Cengiz Yakinci; Mucahit Egri (Indonesian Pediatric Society Publishing House, 2017)
We assessed prospectively the prevalence 01 pathologic and Innocent murmurs in childhood, to determine the efficacy of clinical evaluation, to compare the results of physical examinations performed by pediatricians and pediatric cardiologists and echocardiographic evaluations, and to contribute to the determination of the limits of echocardiography indications in children with murmurs. A number of 8647 children, aged 6.5-15 years, 4092 females, 4455 males in ten different primary schools belonging to different socioeconomic levels in Malatya, Eastern Turkey. Those children with a murmur were evaluated by a pediatric cardiologist. Chest X-ray, electrocardiography, and echocardlography were obtained in all subjects having a murmur. The results of physical examinations performed by the pediatricians and the pediatric cardiologist were compared, and the final diagnoses were reached by evaluation of chest X-ray, ECG and chocardiography. The incidence of Innocent murmurs was found to be 3.4% and that of pathological murmurs 0.54% In the population eximaned. The statistical comparison of the results revealed that pediatricians have a tendency toward Innocent murmurs in the interpretation of murmurs (p<0.05). There was not a statistically significant difference between the results of physical examinations of the pediatric cardiologist and the results of echocardlographic examination. Pediatricians can diagnose pathologic cases with a sensitivity of 63.8% whereas pediatric cardiologist could diagnose those cases with a sensitivity of 95.7% and specificity of 99.7%. Our findings support the policy that children with a cardiac murmur should be referred to a pediatric cardiologist, in order to verify clinical diagnosis.